An assessment of government-funded small-scale cage fish farming in Siavonga District, Zambia: performance, challenges and opportunities - Hasimuna, Oliver J.; Mphande, Joseph; Lengwe, Moses; Siavwapa, Sillah; Bwalya, Henry; Ndhlovu, Ipaalo; Muloongo, Malambo; Bbole, Ian; Siankwilimba, Enock; Ogundare, Isaac O.; Jere, Arthertone; Mbaimbai, Francis M.; et al. (Frontiers in Sustainable Food Systems, 2025)
Aquaculture is a key driver of food and nutrition security, rural livelihoods, and economic development in Zambia. This study evaluated the performance, challenges, and opportunities associated with government-funded small-scale cage fish farming in Siavonga District, contributing to the discourse on sustainable aquatic food systems and climate resilience. Using mixed methods including questionnaires, interviews, and insights from the Ministry of Fisheries, data were gathered from 30 purposively selected farmers between 2020 and 2023. The findings show that government investments have improved income generation and job creation by lowering entry barriers through infrastructure support and extension services. However, constraints such as theft, fish predation, currency fluctuations, and bureaucratic inefficiencies continue to hinder adaptive decision-making and reduce the competitiveness of publicly supported farmers compared to their private-sector counterparts. Key opportunities for sustainable transformation include expanding access to quality inputs such as fingerlings and feed, improving lake transport systems, and fostering public-private partnerships. Importantly, this study offers a climate-smart perspective by highlighting how adaptive support systems and inclusive policy frameworks can enhance the resilience of small-scale aquaculture in the face of climate variability. Integrating government-led initiatives with market-driven innovations is essential to strengthen the resilience, inclusivity, and long-term viability of Zambia’s aquaculture sector. The study provides practical insights for advancing blue transformation in similar socio-ecological settings.